Electrospun Nanofibers for Wound Management. Issue 7 (17th November 2021) - John, Johnson V.; McCarthy, Alec; Karan, Anik; Xie, Jingwei
Abstract: Electrospun nanofibers show great potential in biomedical applications. This minireview traces the recent advances in electrospun nanofibers for wound management via various approaches. Initially, we provide a short note on the four phases of wound healing, including hemostasis, inflammation, proliferation, and remodeling. Then, we state how the nanofiber dressings can stop bleeding and reduce the pain. Following that, we discuss the delivery of therapeutics and cells using different types of nanofibers for enhancing cell migration, angiogenesis, and re‐epithelialization, resulting in the promotion of wound healing. Finally, we present the conclusions and future perspectives regarding the use of electrospun nanofibers for wound management. Abstract : In this minireview, we summarized the recent advances of electrospun nanofiber‐based wound dressings to control pain, hemorrhage, infection, cell migration, remodeling, and angiogenesis.